Polygonal contact model for magnetic track brake simulations: Utilization of the Polygonal contact model within SIMPACK for simulations of magnetic track brakes - Červenka, Jakub (My University, 2025)
This thesis examines the applicability of the Polygonal Contact Model (PCM) for the simulation of contact between the magnetic track brake and the rail. Since improved braking performance is the key for further optimization of the railway system while maintaining high safety standards, accurate and efficient contact modeling approaches are essential. The aim of this study is to evaluate the accuracy of the Polygonal Contact Model implementation in the software Simpack 2025x.1 for the magnetic track brake application. Two scenarios are examined in this thesis. Results of a paraboloid indenter being pressed onto an elastic halfspace are compared to an analytical solution for this problem. The impact of PCM using elastic bodies is also studied on this case. This thesis also describes the preprocessing in Abaqus necessary in order to successfully implement the elastic extension PCM. The viability of use for the railway application is further judged by simulating a new and a worn brake shoe being pressed onto a straight rail.
Keywords: Polygonal Contact Model; Magnetic track brake; Contact modelling; Pole shoe; Simpack; Elastic extension PCM; Abaqus